Pro secrets to dramatic digital photos - Zuckerman, Jim (Lark photography book, 2011)
The author, a photographer known for his vivid, surreal images, reveals a lifetime's worth of tricks and techniques for taking photos with that huge wow factor. In this title, his pro secrets range from the technical to the abstract, from making an impact with complementary colours to getting picture-postcard photos of scenic sites